UPAYA PENINGKATAN HASIL BELAJAR SHOOTING DALAM BOLA BASKET MELALUI PERMAINAN RING GANDA (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine how the implementation of development programs and how-owned facilities and infrastructure to support development programs in Krengseng Sejati School Football. The population in this study were athletes and coaches in Krengseng Sejati School Football , Gringsing sub-district, Batang city. The sample in this study were athletes and coaches in Krengseng Sejati School Football , Gringsing sub-district, Batang city as much as a coach and 30 athletes. Sampling technique used is total sampling. Data collection by survey method with questionnaire. Data from the instrument questionnaire prepared by the method of analytical description of the percentage. From the analysis shows that the pattern Soccer School coaching very well categorized by 4 respondents (19%), categorized either as many as 21 respondents (68%), categorized simply by 4 respondents (13%), and no one category is less and less . The conclusion that can be taken was the average rate of pattern formation Krengseng Sejati School Football , Gringsing sub-district, Batang city was 77%. These results indicate that the pattern of development is in good category.